KINESIO TAPING INFLUENCE THE AGILITY OF RECREATIONAL SOCCER PLAYERS - Robby Robby; Aditya Paramita Andini; Tanti Ajoe Kesoema (Jurnal Kedokteran Diponegoro)
Background: Soccer is a physical activity that requires good agility to run fast, dribble the ball, avoid opponents and guard opponents. Kinesio taping is used in rehabilitation, especially for the treatment and prevention of musculoskeletal system injuries, but there is not enough data in increasing the agility of soccer player. Methods: This study was a quasi-experimental with a pre-post test group design on 60 males aged 17-25 years who played recreational soccer. Subjects were divided into 2 groups consisting of intervention group (n = 30) and control group (n = 30). The intervention group received kinesio taping with a facilitation technique with a 35% pull on the quadriceps, gastrocnemius and soleus muscles, while the control group received sham, non-elastic adhesive tape on the same muscle group. Agility measurements were carried out before and after 30 minutes of intervention using the Agility T Test in both groups. Results: There was no statistically significant difference in the average agility score before intervention between the control group (11.38+0.83 seconds) and the treatment group (11.47+1.20 seconds) with p=0.7304. In control group, there was no statistically significant difference in the average agility score before (11.38+0.83 seconds) and after (11.40+0.79 seconds) the intevention (p=0.6184). In intervention group, there was a statistically significant difference in the average agility score before (11.47+1.20) and after (10.99+1.20) intervention (p=0.000). Discussion: The facilitation technique of kinesio taping increases muscle strength and muscle contraction leading to increased agility. Conclusion: Kinesio taping increase the agility of recreational soccer player.